Respingimenti “sommari” alla frontiera e migranti “disobbedienti”: dalla Corte di Strasburgo un overruling inaspettato nel caso ND e NT c. Spagna - Bernardini, Lorenzo (Cultura giuridica e diritto vivente, 2020)
[“Hasty” push-backs at the border and “reluctant” migrants: an unpredicted overruling in the ND and NT v. Spain case from ECtHR] This paper aims to analyse whether a recent decision of the ECtHR concerning hasty push-backs at the border of Mellila against irregular migrants may breach the fundamental guarantees enshrined in the ECHR. In particular, the main ECHR legal framework vis-à-vis “collective expulsions” and “effective remedy” will be outlined, in order to understand how the Court might have overruled its well-established case-law on the matter. Whilst the Court sets forth some crucial statements regarding the intangibility of international obligations, this decision looks as if it nonetheless could allow dangerous practices to be implemented by borders authorities, namely the possibility to expel foreigners without providing them with an effective and individualised exam upon their status, due to their blameworthy conduct.